1997
DOI: 10.1038/nm1297-1354
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of malignant brain tumors by intratumoral implantation of retroviral vector-producing cells

Abstract: Intratumoral implantation of murine cells modified to produce retroviral vectors containing the herpes simplex virus-thymidine kinase (HSV-TK) gene induces regression of experimental brain tumors in rodents after ganciclovir (GCV) administration. We evaluated this approach in 15 patients with progressive growth of recurrent malignant brain tumors. Antitumor activity was detected in five of the smaller tumors (1.4 +/- 0.5 ml). In situ hybridization for HSV-TK demonstrated survival of vector-producing cells (VPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
392
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 622 publications
(398 citation statements)
references
References 21 publications
4
392
0
2
Order By: Relevance
“…This is exemplified by two unsuccessful phase III randomized controlled trials of gene therapy16, 17 and variable responses in other smaller clinical studies 6, 18, 19, 20, 21…”
Section: Introductionmentioning
confidence: 99%
“…This is exemplified by two unsuccessful phase III randomized controlled trials of gene therapy16, 17 and variable responses in other smaller clinical studies 6, 18, 19, 20, 21…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is a strong limitation for the treatment of solid tumors with retroviral vectors using the herpes simplex virus thymidine kinase (TK)/ganciclovir (GCV) strategy. 1,2 In this suicide gene therapy approach, the TK enzyme transforms the nucleosidic analog GCV into GCV-monophosphate, which is subsequently converted into the di-and triphosphate forms by cellular kinases. 3 Then, the GCVtriphosphate is incorporated into elongating DNA, which can lead to the death of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Despite very encouraging preclinical trials, this strategy has so far not shown great success in patients. The efficiency of TK gene transfer with retroviral vectors reported in some clinical trials was extremely low, 1,2 and it could in part explain the disappointing results observed in patients. 1,11 We could assume that it should be possible to increase the efficiency of gene transfer by using the latest generation of packaging cell lines that produce high-titer recombinant retroviruses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Results of clinical trials of HSV-tk/GCV therapy, however, have been disappointing. 4,5 Thus, we attempted to develop a strategy that would improve the performance of HSV-tk/GCV therapy when applied in combination.…”
Section: Introductionmentioning
confidence: 99%